GRADUATE EDUCATORS AND ELEMENTARY TEACHER: TRAINING STRATEGIES IN PHYSICAL EDUCATION (Fiep Bulletin - online, 2014)
Training strategies in Physical Education (PE) requires adaptation and diversity. Thus, the conceptual framework for the promotion and strengthening knowledge about the area of PE matter not only clarify their educational goals (e.g. motor activity, physical education, sport and physical activities and sport) for the development and learning of all children, arising from each educational context (daycare, preschool, elementary school physical education, physical activity and sport, physical activity, informal sport and federated sport), but also the development of skills of observation, analysis and reflection on the motor actions, the sport techniques and processes of development and learning in the early years. Data were collected through individual questionnaires among students of 1st year Bachelor in Basic Education (BBE ), under of the curricular unit of Expression and Motor Education (EME ). The data on the perception of effectiveness of training strategies in learning and consolidation of expertise were collected through a closed question requesting the identification of five “best or most effective in terms of learning” training strategies used at curricular unit EME , inserted the individual questionnaire answered by 59 students of 1st year BBE . The results point towards the students identify a “spot” exceeding 53.8% (157) of the total references in training strategies “Practice experiential Motor Activities and Sport and Physical Activities”, “Video observation” and “Fieldwork” as the most effective in terms of learning. Thus students seem to value more training strategies with a high level of personal involvement and attachment.
Keywords: training; content knowledge; physical education